Decision-Making on Repeat Purchases of Goat and Sheep Farmers: Evidence of the "Akar Rumput" Cooperative - Rizki Yunus Firmansyah; Suci Paramitasari Syahlani (JURNAL TRITON, 2025)
The high demand for goats and sheep in Indonesia has encouraged livestock cooperatives to use imported livestock as a genetic source to increase productivity. This study aims to identify the influence of the quality of imported goats and sheep and the service quality provided by the Grassroots Breeders' Cooperative (PAR) on the repurchase behavior of goats and sheep breeds. The research was conducted survey design from September to October 2023. The population of this study was the goat or sheep farmers who had experience of buying imported goats or sheep. The sample was determined using the judgmental sampling method with the respondent criteria (1) goat and sheep farmers (2) had experience to purchases imported goats or sheep from the PAR Cooperative. Data were analyzed using descriptive analysis and multiple linear regression. The results show that the product quality of imported goats and sheep significantly affected repurchase behavior of imported livestock from the PAR Cooperative with β=0.917. Meanwhile the quality of service had no effect on the repurchase behavior of imported goats and sheep with β=0.144. These results conclude that the provision of imported goats and sheep that are in accordance with the required genetic quality, determines the decision of farmers to rebuy imported livestock from the PAR Cooperative.